FLIGHTS BY FOREIGN CIVIL AIRCRAFT TO SOUTH AFRICA - Ploeger, Jan (Scientia Militaria - South African Journal of Military Studies, 2012)
Legislation enabling effect to be given to the International Convention for regulating air navigation, and to make provision for the control, guidance and encouragement of flying within the Union of South Africa and for other purposes incidental thereto, for all purposes known as the Union Aviation Act [No. 16 of 1923], was passed on the 23rd of May 1923 to allow effect to be given to the International Air Navigation Convention of 1919, and to make the provisions referred to above.